Leptin Signaling in the Carotid Body Regulates a Hypoxic Ventilatory Response Through Altering TASK Channel Expression - Yuan, Fang; Wang, Hanqiao; Feng, Jiaqi; Wei, Ziqian; Yu, Hongxiao; Zhang, Xiangjian; Zhang, Yi; Wang, Sheng (Frontiers in Physiology, 2018)
Leptin is an adipose-derived hormone that plays an important role in the regulation of breathing. It has been demonstrated that obesity-related hypoventilation or apnea is closely associated with leptin signaling pathways. Perturbations of leptin signaling probably contribute to the reduced sensitivity of respiratory chemoreceptors to hypoxia/hypercapnia. However, the underlying mechanism remains incompletely understood. The present study is to test the hypothesis that leptin signaling contributes to modulating a hypoxic ventilatory response. The respiratory function was assessed in conscious obese Zucker rats or lean littermates treated with an injection of leptin. During exposure to hypoxia, the change in minute ventilation was lower in obese Zucker rats than chow-fed lean littermates or high fat diet-fed littermates. Such a change was abolished in all groups after carotid body denervation. In addition, the expression of phosphorylated signal transducers and activators of transcription 3 (pSTAT3)，as well as putative O2-sensitive K+ channels including TASK-1, TASK-3 and TASK-2 in the carotid body，was significantly reduced in obese Zucker rats compared with the other two phenotype littermates. Chronic administration of leptin in chow-fed lean Zucker rats failed to alter basal ventilation but vigorously increased tidal volume, respiratory frequency, and therefore minute volume during exposure to hypoxia. Likewise, carotid body denervation abolished such an effect. In addition, systemic leptin elicited enhanced expression of pSTAT3 and TASK channels. In conclusion, these data demonstrate that leptin signaling facilitates hypoxic ventilatory responses probably through upregulation of pSTAT3 and TASK channels in the carotid body. These findings may help to better understand the pathogenic mechanism of obesity-related hypoventilation or apnea.